Harmonisation of Methods and Measurements in the Fight against doping (1999)
The European Union has pledged to support the fight against doping in sport. A preliminary project known as Hardop 'Harmonisation of methods and measurements in the fight against doping', funded in 1998 by the European Union, set out to identify the research necessary to improve the way in which doping in sport is being combated. The project's final report, published in 1999, stressed the need for new developments not only in measurement and testing technologies, but also in co-ordination and education.